Implementation of Cabaritus Method to Improve Students’ Presentation Skill in Learning - Bayu Wijayanto, Bayu Wijayanto; Susetyo, Bigharta Bekti; Rahmanelli, Rahmanelli; Nofrion, Nofrion (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This research was conducted to increase students’ participation in delivering ideas/notions/opinions in lectures and improve the quality of student presentations through the application of the CABARITUS method. The type of research is classroom action research while the action giver is lecturer and the research subjects are 45 students who take the Curriculum and Geography Textbooks Study. Data about students who are active during lectures was collected by observation using a checklist sheet. While data about the quality of student presentations were collected by observation using learning observation sheets. Data were analyzed using percentage techniques. The results showed that; 1) the number of students who actively gave presentations in the form of ideas/opinions at the first meeting was 11 people (24.44%), at the second meeting there were 16 people (35.55%) and at the third meeting were 21 people (46.66 %). This result can be interpreted that the application of the CABARITUS method can increase the number of students who actively deliver ideas/notions/opinions in lectures. 2) In terms of the quality of presentations at the first meeting, from 11 students who made presentations there were only two students who were able to deliver it in the excellent category (18.18%), at the second meeting they rose to 5 from 16 students (31.25%) and at the third meeting 9 out of 21 (51.38%) students had very good presentation quality. The quality of the presentation can be seen in the presentation content and presentation techniques. The conclusion from this research is that CABARITUS method can increase the number of students who make learning presentations and improve the quality of student learning presentations